PENGEMBANGAN MODEL PEMBELAJARAN JASMANI ADAPTIF UNTUK OPTIMALISASI OTAK ANAK TUNAGRAHITA - Sumaryanti Sumaryanti (Universitas Negeri Yogyakarta, 2010)
The purpose of this study is to set adapted physical learning model for optimize mental retarded brain. This objectives achieved in two stages, for two years.Research and Development approach are applied in this research in two stages. Phase I conducted literature review and field observations. Data that obtained in this phase are analyzed and are used to set a draf of adapted physical learning model to optimize mental retarded brain. The result of Phase I (2009) includes the literature review about the characteristics of mental retarded children, the motion effects on the brain, gestures to the brain. Field observation that carried out in this phase obtain that motor skill of mental retarded child are good running, lack of balance, less category in cognitive abilities. The ability to read, write, and arithmetic are in moderate category. Affective abilities in self-control is in moderate category, but the empathy and cooperation into well category. Psychomotor ability to perform activities of daily life in the good category. The model of motion exercises and songs combined with circuit activities to optimize the mental retarded brain. The entire 40-minute duration of learning, with 9 minutes of the first and last songs of the motion and shape of gymnastics and the remaining circuit events consisting of 6 stations that include trampoline, crawling, climbing beam bridges, rolling over, facedown on the medicine ball, and crawling in the aisle